Eficiencia y eficacia administrativa de los Servidores Públicos de la Dirección Distrital 13D06 Junín-Bolívar salud - Vargas Zambrano, Angela Patricia (2020)
The present investigation was carried out with the objective of evaluating the administrative efficiency and effectiveness of the public servants of the District Directorate 13D06 Junín-Bolívar Health, the information was collected by means of the inductive, deductive and analytical methods in which the scientific theories that give theoretical support to the research were analyzed, in addition to helping the development of the activities where the POA of the institution was studied, which It allowed knowing the degree of achievement of the objectives. Investigative techniques were used, such as the interview with the director of the institution, who announced that an evaluation is carried out once a year; It also maintains that they use management indicators that determine Health for the preparation of the POA, which is evaluated quarterly by means of signs and is monitored under a matrix that includes four parameters: goal, time, expenditure by source and indicators. Finally, to counteract the problems encountered, strategies were created to improve the administrative management of the institution's public servants.